How To Implement This Function With 2 Input Nand

  • #1
transgalactic
1,395
0
Default How To Implement This Function With 2 Input Nand..
(+) =XOR

F(w,x,y,z)=(w'+x'+y')(+)xyz

i tried to :

F(w,x,y,z)=(w'+x'+y')(+)xyz=(w'+x'+y')' *(xyz) + (w'+x'+y')(xyz)'=
=(wxy)(xyz)+(w'+x'+y')(x'+y'+z')
..
..
in the end i get
=wxyz+w'x'+w'y'+w'z'+x'+x'y'+x'y'+y'+y'z'+y'z'

what to do know?
how to transform implement it with a two input line NANDs
?
 

Answers and Replies

  • #2
misho
19
0
Well, the word NAND should scream Sum of Products (SOP), so try to get your function to that point, then you can modify it further. After playing around with your function, you should get something like:

[tex]F = \overline{x} + \overline{y} + (\overline{w})(\overline{z}) + wxyz[/tex]

(Keep in mind that [tex]A+AB = A[/tex]; your final equation doesn't take that into account).

I'm going to show you another useful proof:

[tex]\overline{ABCD} = \overline{A}+\overline{B}+\overline{C}+\overline{D} = (\overline{A}+\overline{B})+(\overline{C}+\overline{D}) = \overline{AB}+\overline{CD} = \overline{(\overline{AB})(\overline{CD})} [/tex]

The function is also equal to (through DeMorgan):
[tex]F = \overline{xy ( \overline{ \bar{w} \bar{z} })( \overline{wxyz}) }[/tex]

Use the proof above on that form of F. Use the proof above to get [tex]\overline{(wxyz)}[/tex], too. Use NANDs as inverters to get w' and z'.
 
  • #3
Zayer
21
0
I think There is a mistake it should be [tex] \overline{AB}+\overline{CD} = \overline{({AB})({CD})} [/tex]
 

Suggested for: How To Implement This Function With 2 Input Nand

  • Last Post
Replies
6
Views
345
Replies
3
Views
256
  • Last Post
Replies
3
Views
603
  • Last Post
Replies
4
Views
400
  • Last Post
Replies
2
Views
390
Replies
16
Views
426
  • Last Post
Replies
6
Views
398
Replies
7
Views
2K
Replies
2
Views
203
Top